The Path of Ostracism: Justice in the Andes and the Negation of Reciprocity in Guaman Poma de Ayala - Berríos-Campos, Claudia (2020)
The Nueva corónica y buen gobierno noted that early colonial Andean society became a world “upside down” in which justice does not keep social balance. This article examines Guaman Poma’s assessment of the administration of justice in the Andean world in his work’s “Primer capítulo de la Justicia”. It looks into the implementation of punishment and its consequences on the individual’s social place in the Andeancommunity. Through the topics of justice and punishment, and the author’s narration of his journey to Ciudad de los Reyes (Lima) in the chapter “Camina el autor”, I observe an Andean version of ostracism:a physical seclusion with possibilities of integration and the social condemnation of a wakcha (orphan) due to the lack of reciprocity and the spiritual exile. In addition, the author’s spiritual ostracism is his own sacrifce to bring justice to the Andean world.